2020
DOI: 10.1523/jneurosci.2106-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high-resolution fMRI of Human Ventral Temporal Cortex Reveals Differential Representation of Categories and Domains

Abstract: Human ventral temporal cortex (VTC) is critical for visual recognition. It is thought that this ability is supported by large-scale patterns of activity across VTC that contain information about visual categories. However, it is unknown how category representations in VTC are organized at the submillimeter scale and across cortical depths. To fill this gap in knowledge, we measured BOLD responses in medial and lateral VTC to images spanning 10 categories from five domains (written characters, bodies, faces, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 102 publications
(157 reference statements)
1
19
0
Order By: Relevance
“…For sighted subjects viewing video stimuli, we found the typical cortical patterns of category selectivity in VTC (Grill-Spector and Weiner et al, 2014;Margalit et al, 2020). This is visible in the representative example sighted subject ( Fig.…”
Section: The Reliability Of Distributed Category Selectivity In Vtc Asupporting
confidence: 56%
“…For sighted subjects viewing video stimuli, we found the typical cortical patterns of category selectivity in VTC (Grill-Spector and Weiner et al, 2014;Margalit et al, 2020). This is visible in the representative example sighted subject ( Fig.…”
Section: The Reliability Of Distributed Category Selectivity In Vtc Asupporting
confidence: 56%
“…Here, we investigate the relative strength of retinotopy and category-selectivity directly by presenting face and scene stimuli to either the left or right visual field, thereby making the stimuli exclusively available (initially) to one hemisphere at a time. Although only providing a limited sampling of the dimensions of space and category, we chose these particular categories and visual field positions because these provide a strong test of interaction between category and visual field positions: visual cortex is known to contain multiple face and scene preferring regions with divergent and strong preferences between these categories (Julian et al 2012;Weiner et al 2018;Margalit et al 2020), that are typically shown to produce the strongest contrast in response between categories. Further, the difference between contralateral and ipsilateral visual fields is typically the strongest retinotopic effect observed (Silson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent high-resolution fMRI with humans has shown columnar-like structures in V1 [42] , [43] , V2 and V3 [44] , V3a [45] , hMT [46] , and ventral temporal cortex showing differential representations of categories and domains [47] . Of particular relevance is the recent study by Schneider et al [48] in which high resolution fMRI provided proof that in the human middle temporal visual complex, columnar clusters meet the criteria of content-specific neural correlates of consciousness (NCC).…”
Section: Dimensional-systems Model (Dsm)mentioning
confidence: 99%